Investigation of teachers' perceptions of organizational citizenship behavior and their evaluation in terms of educational administration - Avcı, Ahmet (Academic Journals, 2016)
The aim of this study is to investigate teachers' perceptions of organizational citizenship behaviors and to evaluate them in terms of educational administration. Descriptive survey model was used in the research. The data of the research were obtained from 1,613 teachers working in public and private schools subjected to Ministry of National Education in Uskudar District of Istanbul province in 2014. In this study, data were obtained from the "Personal Information Form" developed by the researcher and from the "Organizational Citizenship Scale". According to research results; teachers had a high level of positive opinions with regard to organizational citizenship behaviors. The opinions of the respondents varied significantly according to gender, professional seniority, state of education and the working time at the school where they worked. High level of organizational citizenship behaviours in the school will affect education activities in positive way, contribute in generating a healthy school climate and influence students’ success in positive way too.
Keywords: Organizational citizenship behaviors; Education management; School